2016
DOI: 10.1089/trgh.2016.0019
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Gaps in Primary Care Preventative Health Services for Transgender Patients: A Systematic Review

Abstract: Purpose: Transgender people face barriers to accessing healthcare, resulting in population-level disparities in health outcomes. Little research is available to better understand the receipt of primary healthcare among transgender patients or how the rate of receipt of preventive care may differ among transgender populations.Methods: The medical literature regarding U.S. adult transgender primary healthcare was reviewed using a keyword search strategy: transgender OR transsexual OR transvestite OR gender nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 70 publications
2
68
0
Order By: Relevance
“…4,7 Some transgender people may also delay transition-related care that is essential to their health and well-being, which would preclude them from being visible in claim records. As a result, our study may underestimate the number of TMBs-they may simply avoid care or the care that they receive may not be captured by the ICD-9-CM codes used in our research.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 Some transgender people may also delay transition-related care that is essential to their health and well-being, which would preclude them from being visible in claim records. As a result, our study may underestimate the number of TMBs-they may simply avoid care or the care that they receive may not be captured by the ICD-9-CM codes used in our research.…”
Section: Limitationsmentioning
confidence: 99%
“…3 Still other people do not identify within the gender binary and may use terms such as gender nonconforming, nonbinary, or gender queer. 4,5 Keeping the challenges of data collection in mind, there are passive methods for identifying likely transgender individuals through administrative data that do not require the person to self-identify. [6][7][8] There are known health disparities for transgender adults, including increased cigarette smoking, elevated risk of depression, and attempted suicide.…”
mentioning
confidence: 99%
“…Research on adjuvant transgender interventions, such as speech therapy, is also insufficient, while patients’ satisfaction with the outcomes of hormonal treatment has not yet been explored (Feldman et al ). Through the review of the literature, Edmiston et al () identified areas of concentration for future research on the subgroups of the transgender community. These groups included transgender men of color, the elderly and individuals living in southern states (Edmiston et al ).…”
Section: Gaps In Researchmentioning
confidence: 99%
“…Through the review of the literature, Edmiston et al () identified areas of concentration for future research on the subgroups of the transgender community. These groups included transgender men of color, the elderly and individuals living in southern states (Edmiston et al ). The findings of this review suggest that preventive healthcare, as well as the development of health promotion, is much needed among the transgender population.…”
Section: Gaps In Researchmentioning
confidence: 99%
“…Clinicians of all na ons must ensure that the emerging science on transgender persons remains an essen al part of this debate ensuring the rights of these, and indeed, all human beings. For example, recent studies around the world have shown li le instruc on in medical schools and li le consensus around the 38,39 type material medical students should learn.…”
Section: Greydanus De Codde Jmentioning
confidence: 99%